CULTURAL DOMAINS: TRANSLATION PROBLEMS CULTURAL DOMAINS: TRANSLATION PROBLEMS - Isabel Negro Alousque (Revista de Lingüística y Lenguas Aplicadas, 2009)
Much of the lexis of a language has a cultural referent and is thus specific to a speech community. The meaning of culturally marked words is often difficult to grasp without some cultural knowledge and poses translation problems, particularly when the words are associated with cultural domains (Nida, 2001). In the present paper we focus on the French cultural domain of cooking. After outlining the elements of the domain, we analyse the difficulties in translating the lexical units from the domain and the range of translation procedures which try to account for their meaning. Much of the lexis of a language has a cultural referent and is thus specific to a speech community. The meaning of culturally marked words is often difficult to grasp without some cultural knowledge and poses translation problems, particularly when the words are associated with cultural domains (Nida, 2001). In the present paper we focus on the French cultural domain of cooking. After outlining the elements of the domain, we analyse the difficulties in translating the lexical units from the domain and the range of translation procedures which try to account for their meaning.